Mucosal-associated invariant T cells in hematological malignancies: Current knowledge, pending questions - Treiner, Emmanuel (Frontiers in Immunology, 2023)
Non-classical HLA restricted T cell subsets such as gamma/delta T and NK-T cells are showing promises for immune-based therapy of hematological malignancies. Mucosal-Associated Invariant T cells (MAIT) belong to this family of innate-like T cell subsets and are the focus of many studies on infectious diseases, owing to their unusual recognition of bacterial/fungal metabolites. Their ability to produce type 1 cytokines (IFNgamma, TNFalpha) as well as cytotoxic effector molecules endows them with potential anti-tumor functions. However, their contribution to tumor surveillance in solid cancers is unclear, and only few studies have specifically focus on MAIT cells in blood cancers. In this review, we wish to recapitulate our current knowledge on MAIT cells biology in hematological neoplasms, at diagnosis and/or during treatment, as well as tentative approaches to target them as therapeutic tools. We also wish to take this opportunity to briefly elaborate on what we think are important question to address in this field, as well as potential limitations to overcome in order to make MAIT cells the basis of future, novel therapies for hematological cancers.